ICT Usage for Primary School Administration in Nigeria: Challenges and Way Forward - Ogunode Niyi Jacob; Nasir Dahir; Yahaya Danjuma M.; Deborah Jegede (International Journal on Human-Computing Studies, 2021)
The administration of primary school education in Nigeria is plagued with problems. One of the problems hindering the effective administration of primary school education is the poor usage of information communication and technology. This paper discussed the challenges of sing ICT for the administration of primary school education. Secondary data and primary school data were sourced from print materials and online publication. The paper identified: inadequate funding of ICT programme, inadequate ICT facilities, poor implementation of ICT policies, poor computer literacy of admin staff, unstable power supply, poor internet services and high cost of ICT facilities. To solve these problem, the paper hereby recommends that the government should provide the primary schools in the Country with adequate ICT facilities. The government should increase the funding of ICT programme in the public primary schools in Nigeria and the government should organize constant training and retraining programme for primary school administrative staff and school administrators etc.